Increasing Public Awareness Related To Early Detection Of Diabetes Mellitus In Jatimekar Bekasi Village - inggraini, Maulin; Andryan Ilsan, Noor; Nurfajriah, Siti; Amelia, Ria; Maya Sari, Elfira (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Noncommunicable Diseases (NCDs) are a serious threat not only for the elderly but also for the young. Based on a report from the International Diabetes Federation (IDF) by 2022 that 1.57 million of the 8.75 million people living with type 1 diabetes worldwide in 2022 are less than 20 years old. This shows the importance of increasing public awareness about Diabetes Mellitus (DM). This PKM is carried out by providing education about the prevention and dangers of DM, then followed by a Temporary Blood Sugar (TBS) examination in the Jatimekar Bekasi village using brochure media. The increas in participantsÔÇÖs knowledge was carried out by analyzing the pre-test and post-test descriptively. The results of the study showed an increase in public knowledge about DM. this can be seen from the increase in post-test result compared to pre-test scores. GDS examination results include risk characteristics of 86.96% (110-200 mg/dL) and DM 13.04 % (>200 mg/dL). There are 3 counseling participants who suffer from DM and have a history of unhealthy eating patterns and not doing physical activity.